Reverberation of Classical Subjects and Forms in the Art Commissions of the Emperor Maximilian I of Habsburg - Frolova, Liudmila V. (Actual Problems of Theory and History of Art, 2015)
Influence of Classical antiquity upon official art at the court of the Emperor Maximilian I of Habsburg is an actual problem that has never been specially considered before. Subjects, images and forms elaborated in the Classical world are displayed in the works of art designed by German artists according to Maximilian’s order. It is evident, for instance, in his cenotaph (1511–1563, Innsbruck, Hofkirche), woodcut series “Triumphal Procession” (1516–1519) and “Arch of Honor” (1515), illustrations to the Emperor’s autobiographical novel “Weisskunig” (ca 1512–1519). Certain historical and mythological characters played a special role in the Emperor’s self-presentation — Roman emperors and mythological characters like Apollo, muses, and satyrs are among them. Various Classical subjects and forms were highly valued by the Emperor, his counselors and artists. Maximilian I paid attention to Classical military and ecclesiastical history. Scholars, who worked out the programme of the Emperor’s official art and propaganda by means of fine arts, considered Classical period as a cradle of science, education and fine arts. Artists took Classical and modern Italian pieces of art, which were regarded as genuine Classical art works, for a model. Ancient and also Italian Renaissance coins, medals and woodcuts are possible sources of Classical forms for the masters from Maximilian’s milieu. A. Dürer and some other masters of his circle attempted to reconstruct Classical regulations on depicting human being’s proportions. This search and efforts are also evidet in the works, created for Maximilian I.
Keywords: Maximilian I; “Triumphal Procession”; “Arch of Honor”; Cenotaph Maximilian I; classical subjects; Albrecht Dürer